Proceedings Lifelong Learning Research Conference (2nd, University of Maryland, College Park, Maryland, February 1-2, 1980) - Whaples, Gene C.; Ewert, D. Merrill; Maryland Univ., College Park. Dept. of Agriculture and Extension Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
Proceedings are presented of the second annual Lifelong Learning Conference, which was designed to build interagency linkages. Papers included deal with environmental/leisure education issues, adult/continuing education concerns, community development, international education, volunteerism, adult basic education, and research methodology. Each paper is summarized in a two-page abstract with bibliography. Among the numerous papers represented are (1) Motivational Typology of Adults Returning to College, (2) The Social and Political Ramifications of Research Reflecting the Exclusiveness of Continuing Education, (3) Conceptual Analysis and Adult Education, (4) Development of an Instrument to Measure the Teaching Behavior of Adult Educators, and (5) Participatory Planning in Lifelong Learning. (LRA)
ERIC Note: Not available in paper copy due to small print.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Abstracts; Adult Basic Education; Adult Education; Adult Learning; Adult Programs; Adults; Community Development; Conference Reports; Educational Research; Environmental Education; International Programs; Lifelong Learning; Research Methodology; Volunteers; Reference Materials, Bibliographies; Collected Works, Proceedings